2002
DOI: 10.1021/jp0215163
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Effect of the Imidazole Ring Orientation on the EPR Parameters for Vanadyl−Imidazole Complexes

Abstract: The vanadium hyperfine coupling constant for vanadyl−imidazole complexes depends on the orientation of the imidazole ring with respect to the vanadyl bond as illustrated by a recent electron paramagnetic resonance (EPR) study of vanadyl−imidazole model complexes (Pecoraro, et al. J. Am. Chem. Soc. 2000, 122, 767). In the study reported here, density functional theory (DFT) calculations of EPR hyperfine and quadrupole coupling constants for a model complex, [VO(imid)(H2O)4]2+, were used to elucidate the orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 49 publications
(143 reference statements)
5
33
3
Order By: Relevance
“…In these and earlier studies, water hydrogen and imidazole nitrogen couplings were found to experimentally depend on the dihedral angle containing the vanadyl unpaired d-orbital and the O–H bond for the water complex45 or the coordinated nitrogen pπ-orbital direction for the imidazole complex51. These variations were subsequently found to be in very good agreement with those theoretically determined45,46. Apparently for copper-amino acid systems, the subtle balance of unpaired electron spin on Cu, N, C α and possibly C β has significant influence on the theoretically computed proton hyperfine couplings.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In these and earlier studies, water hydrogen and imidazole nitrogen couplings were found to experimentally depend on the dihedral angle containing the vanadyl unpaired d-orbital and the O–H bond for the water complex45 or the coordinated nitrogen pπ-orbital direction for the imidazole complex51. These variations were subsequently found to be in very good agreement with those theoretically determined45,46. Apparently for copper-amino acid systems, the subtle balance of unpaired electron spin on Cu, N, C α and possibly C β has significant influence on the theoretically computed proton hyperfine couplings.…”
Section: Resultssupporting
confidence: 80%
“…Although there appears to be some correlation with the amount of spin delocalized on C β and the extreme geometric sensitivity of the a iso ’s for the amino hydrogens, no simple explanation can be devised. The theoretical findings also failed to match successes found by previous QM/DFT studies on vanadyl–water and vanadyl-imidazole complexes45,46. In these and earlier studies, water hydrogen and imidazole nitrogen couplings were found to experimentally depend on the dihedral angle containing the vanadyl unpaired d-orbital and the O–H bond for the water complex45 or the coordinated nitrogen pπ-orbital direction for the imidazole complex51.…”
Section: Resultscontrasting
confidence: 59%
“…In this work, we reexamined the dependence of A N iso on the dihedral angle h and tested for the first time that of A N with respect to that of an equatorial nitrogen [74], we used DFT calculations to elucidate the dependence of A N iso and A N z on the angle between the V=O and V-N bonds, whereN is the coordinated aromatic nitrogen atom (indicated with u); in this case u is varied from 90°to 180°(i.e., from a perfectly equatorial to a perfectly axial imidazole nitrogen).form of sin(2h -90) described by Smith et al[80] for the imidazole contribution to the vanadium hyperfine coupling constant. Interestingly, the value calculated in this work is approximately 11 % smaller than that reported by Saladino and Larsen[81]. The dependence of A N iso and A N z on the angle u between the V=O and V-N bonds is shown inFig.…”
contrasting
confidence: 60%
“…It has been shown experimentally that the A z values of VO 2? imidazole species have a critical angular dependence [80] and this has been reconfirmed through DFT methods [81,82]. A dependence of the 14 N superhyperfine coupling constant tensor A N on the dihedral angle h between the V=O and N-C bonds, where C is the carbon that bridges the two nitrogen atoms in the imidazole ring, has also been proposed [81].…”
Section: Variation Of the 14 N Superhyperfine Coupling Constant With mentioning
confidence: 89%
“…[13] The two expected values are significantly higher than those measured: as discussed later, it is possible to predict the A z value for the two species also by DFT methods, which give results comparable with those experimentally measured. However, by following what was done by Saladino and Larsen [31] for V IV O imidazole species after the fundamental work of Pecoraro and co-workers, [32] we studied through DFT calculations the value of 51 V A z in V…”
Section: ͻ1mentioning
confidence: 99%